2012
DOI: 10.4172/2155-9597.1000153
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Malaria in School Children and Evaluation of the Performance Characteristics of the Partec CyscopeHelen Kuokuo Kimbi, in the Mount Cameroon Region

Abstract: The key to the effective management of malaria is prompt and accurate diagnosis followed by effective treatment. The aim of this study was to determine asymptomatic malaria parasite prevalence and density and evaluate the performance characteristics of the Partec CyScope ® (fluorescent microscope) in school children in the Mount Cameroon region using light microscopy as a gold standard. A total of 541 pupils aged 4 -16 years were recruited into the study. After recording demographic data on each child, capilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 14 publications
6
29
1
Order By: Relevance
“…WHO stipulates a minimal standard of 95% for P. falciparum sensitivity and specificity [2]. The sensitivity and specificity of Partec CyScope ® used in the study falls slightly below the standards set by WHO but are however both greater than 80% and similar to those of Hassan et al [33] and Kimbi et al [11]. Nkrumah et al [9] in Ghana recorded higher performance characteristics with sensitivities of 100% and specificities of 97.4% for Partec CyScope ® .…”
Section: Fig 2 Malaria Prevalence By Light Microscopy In Relation Tmentioning
confidence: 60%
See 2 more Smart Citations
“…WHO stipulates a minimal standard of 95% for P. falciparum sensitivity and specificity [2]. The sensitivity and specificity of Partec CyScope ® used in the study falls slightly below the standards set by WHO but are however both greater than 80% and similar to those of Hassan et al [33] and Kimbi et al [11]. Nkrumah et al [9] in Ghana recorded higher performance characteristics with sensitivities of 100% and specificities of 97.4% for Partec CyScope ® .…”
Section: Fig 2 Malaria Prevalence By Light Microscopy In Relation Tmentioning
confidence: 60%
“…Such tests provide results in 2 to 15 minutes. Two RDTs are most widely used in Cameroon -the 'CareStart TM Malaria HRP2 pf [10], and the Partec CyScope ® [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of this study reported sensitivity, specificity, positive and negative predictive values of 61.8%, 98%, 95.7% and 63.9% respectively against 62.2%, 96%, 95.7% and 63.9% for Giemsa-based method [12]. Besides, fluorescence microscopy is increasingly accepted and used in Cameroon by some researchers [14,15]. This study is aimed at accessing the prevalence and factors associated with malaria, and determining the prevalence of asymptomatic carriage of malaria parasites and fevers of non malarial origin using Light Emitting Diodes (LED) Cyscope fluorescence microscopy.…”
Section: Introductionmentioning
confidence: 74%
“…Children were recruited on a convenient approach in each school through random sampling method. Based on a malaria prevalence of 58.4% with fluorescence microscopy as reported by Kimbi et al [14], the sample size was determined using the Lorentz's formula n = Z 2 pq/d 2 where n = the required sample size, Z=statistic for the desired confidence level (1.96 for 95% confidence level), p = assumed malaria prevalence in schoolchildren, q = 1-p: proportion of malaria negative participants and d = accepted margin of error (5%). The minimum sample size was estimated as n=373.…”
Section: Study Sample Sizementioning
confidence: 99%